Critical review of ribbed solar air heater and performance evaluation of various V-rib configuration. (May 2021) - Nidhul, Kottayat; Yadav, Ajay Kumar; Anish, S.; Kumar, Sachin
Abstract: The low heat transfer rate in a flat plate solar air heater (SAH) is due to the development of a laminar sub-layer near the heated absorber plate. Owing to this, the plate temperature rises substantially, instigating losses and thus reducing the efficiency. Extensive research has been carried out to mitigate this problem, of which passive technique emerged to be a promising solution. The passive method involves the application of fins/turbulators/ribs on the surface where the boundary layer develops so that it breaks the same. Various profiles and configurations of the ribs ranging from transverse to inclined and continuous to discrete have been presented concisely. Correlations on Nusselt number ( Nu ) and friction factor ( f ) for different rib configurations have been summarized in order so that it can be accessed for future research. 3-D CFD analysis is carried out to gain insight into the flow pattern of various V-ribbed SAH, and with the help of streamlines and contours, the findings are established. Furthermore, various exergy destruction has been studied in detail for different V-rib configurations, namely– V-rib, multiple V-rib, and multiple V-rib with the gap, and analyzed in detail for prospective studies. Exergetic performance study of these rib configurations indicates that the multiple ribs and the multiple rib-gap combinations enhance exergetic efficiency ( η ex ) by 12% and 31.6%, respectively, in comparison to V-rib SAH. Highlights: A critical review of ribbed solar air heaters (SAHs) is presented. 3-D CFD analysis is carried out to study the impact of the rib gap on performance. Energy and exergy analysis of SAH with various V-rib configurations are presented. Multiple V-ribs with gap shows 31.6% higher exergetic efficiency compared to V-rib.